Combining ability and heterosis for fiber quality traits in cotton. - Bolek, Yuksel; Bardak, Adem; Cokkızgın, Hatice (Plant Breeding and Seed Science, 2021)
Combining ability analysis and heterosis for cotton fiber quality traits were studied in a set of diallel crosses involving eight cotton (Gossypium sp.) genotypes. Randomized complete block design was used to test 56 F1 and 8 parents for fiber quality traits; length (Len), strength (Str), micronaire (Mic), uniformity (Unf), elongation (Elg), spinning consistency index (Sci) and short fiber index (Sfi). Analysis revealed significant general combining ability (GCA) and specific combining ability (SCA) effects for all the traits and additive gene effects were important in the inheritance of the traits. Giza-45 had the highest GCA effects for Len, Sci, Unf and Elg while Is-4 had the highest Str value. Mic and Sfi values were lowest for Askabat-100 and Giza-45, respectively. The cross Cukurova-1518 × 108-F and Nazilli-84S × Askabat-100 had the lowest SCA effects for Mic and Sfi, respectively. The highest values for Len (Askabat-100 × 108-F), for Str (Acala Prema × 108-F), for Sci (Is-4 × Giza-45), for Unf (Stoneville-453 × Askabat-100) and for Elg (108-F × Is-4) were also obtained. Hybridizations among Askabat-100 × Nazilli-84S, Is-4 × Giza-45, Askabat-100 × Stoneville-453, Askabat-100 × Giza-45, Is-4 × 108F, Giza-45 × 108F, Giza-45 × Acala Prema, Nazilli-84S × Giza-45, Is-4 × Nazilli-84S and Acala Prema × Askabat-100 crosses yielded the best heterosis and heterobeltiosis values. Aforementioned parents and crosses could be utilized for further selection of high fiber quality and applying 3-way crosses or modified backcross or recurrent selection to genotypes having good combining ability would improve fiber quality...